P11 Retrospective analysis to identify the incidence and prevalence of pre-existing chronic liver disease in patients presenting with hyperacute, acute and sub-acute liver failure. (16th November 2010) - Audimoolam, V; Zen, Y; Joshi, D; Bernal, W; Auzinger, G; Willars, C; Portman, B; Heaton, N; O'Grady, J; Heneghan, M; Agarwal, K; Aluvihare, V; et al.
Abstract : Introduction: Liver failure can be classified as hyperacute liver failure (HALF), acute liver failure (ALF), sub-acute liver failure (SALF), acute on chronic liver failure (ACLF) and chronic liver failure. The classification is dependent based upon presentation and the existence of diagnosed or undiagnosed cirrhosis. In individuals presenting with ALF/SALF, liver biopsy is not routinely performed except in exceptional cases because of the increased risk of bleeding due to their coagulopathic state. Hence, the incidence and prevalence of chronic liver disease in patients presenting with ALF/SALF has not been explored. Method: We retrospectively analysed, prospectively collected data from all patients undergoing liver transplantation for ALF/SALF from 2000 to 2010. A single liver histopathologist, blinded to the clinical diagnosis, reviewed the hepatectomy explant specimen. Based on the severity of hepatocyte necrosis, nodular regeneration and chronic inflammatory change four different histopathogical diagnosis were made; ALF, SALF, ACLF and ALF on a background of chronic inflammatory change. Results: A total of 196 patients with a clinical diagnosis of ALF/SALF (152/44, M/F 130:68, a median age 35 (16–69) underwent liver transplantation from 2000 to 2010. 149 patients had both a clinical and histopathological diagnosis in keeping with ALF. Twenty-nine of the 44 SALF patients had a compatible histopathological diagnosis of whom 19 were seronegative one with grade 3–4 siderosis, five autoimmune hepatitis (AIH) and five drug induced (non-paracetamol). Discrepancy between clinical and histopathological findings were observed in 18 patients; three in the ALF group diagnosed histopathologically as SALF (2 Budd Chiari and 1 AIH) and 15 in the SALF group diagnosed histopathologically as ALF (nine sero-neg, four AIH, two drug related). Amongst the clinical ALF group, 11 patients (10 Wilson's, 1 hepatitis B) had evidence of ACLF on histology and five patients (1 HBV, 2 seronegative, 1 Budd Chiari (B.C.) and 1 paracetamol overdose with an h/o excess alcohol) showed evidence of acute liver injury on a background of chronic inflammatory changes without fibrosis or cirrhosis. On comparing the two group's with a clinical diagnosis of ALF/SALF, as expected ALF patients were younger (mean (M) age 31.7 vs 45.3 SALF, p<0.0001), had higher INR (M-6.64 vs 4.2, p<0.0001) and a lower bilirubin (197 vs 405 p<0.0001) Analysis of the survival outcome in patients with a clinical diagnosis of ALF/SALF showed no difference between the two groups—log rank score 0.4, p=0.5. INR correlated negatively with survival in the ALF group (r=−0.244, p<0.003), whereas it was age and creatinine in the SALF group (r=−0.699, p<0.0001 and r=−0.341, p<0.02). Survival among ALF/SALF/ACLF was again not significant (log rank score 2.045, p=0.5). Conclusion: The incidence and prevalence of acute liver injury on a background of chronic inflammatory change is uncommon. In our HALF/ALF/SALF group, apart from Wilson's and one case of HBV no patient had evidence of cirrhosis. The clinical diagnosis of ALF/SALF using accepted criteria (history+imaging) seems to be accurate in the majority of patients without the recourse to a liver biopsy. However, liver biopsy may still be required to define optimal treatment strategies, for example, lymphoma.